The NTP binding site of the polymerase ribozyme - Akoopie, Arvin (Nucleic Acids Res, 2018)
A previously developed RNA polymerase ribozyme uses nucleoside triphosphates (NTPs) to extend a primer 3′-terminus, templated by an RNA template with good fidelity, forming 3′-5′-phosphordiester bonds. Indirect evidence has suggested that the ribozyme's accessory domain binds the NTP with a highly conserved purine-rich loop. To determine the NTP binding site more precisely we evolved the ribozyme for efficient use of 6-thio guanosine triphosphate (6sGTP). 6sGTP never appeared in the evolutionary history of the ribozyme, therefore it was expected that mutations would appear at the NTP binding site, adapting to more efficient binding of 6sGTP. Indeed, the evolution identified three mutations that mediate 200-fold improved incorporation kinetics for 6sGTP. A >50-fold effect resulted from mutation A156U in the purine-rich loop, identifying the NTP binding site. This mutation acted weakly cooperative with two other beneficial mutations, C113U in the P2 stem near the catalytic site, and C79U on the surface of the catalytic domain. The preference pattern of the ribozyme for different NTPs changed when position 156 was mutated, confirming a direct contact between position 156 and the NTP. The results suggest that A156 stabilizes the NTP in the active site by a hydrogen bond to the Hoogsteen face of the NTP.